2016
DOI: 10.3906/biy-1508-31
|View full text |Cite
|
Sign up to set email alerts
|

Sodium borate treatment induces metabolic reprogramming in hepatocellular carcinoma through SIRT3 activation

Abstract: Sirtuins are NAD + -dependent deacetylases and ADP ribosyltransferases that are activated under stress conditions such as calorie restriction and starvation. Boron, which is mostly found in the form of boric acid (BA) or sodium borate (NaB), is known to bind NAD + . In this study, the effect of NaB on hepatoma cell line HEP3B was investigated by analyzing the proteins harvested from NaB-treated and serum-starved HEP3B cells. The NaB treatment (15 µg/mL) led to a decrease in the overall proteome acetylation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Previously, we have demonstrated that sodium perborate causes anti-proliferative and apoptotic effect in HepG2 and Hep3B cell lines 5 . NaB, also a boron derivative, is an effective agent cancer and shows SIRT3 activity in HCC Hep3B cell lines 14 . Although these boron derivative molecules show anti-cancer effect on HCC cells, high killing doses are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have demonstrated that sodium perborate causes anti-proliferative and apoptotic effect in HepG2 and Hep3B cell lines 5 . NaB, also a boron derivative, is an effective agent cancer and shows SIRT3 activity in HCC Hep3B cell lines 14 . Although these boron derivative molecules show anti-cancer effect on HCC cells, high killing doses are needed.…”
Section: Discussionmentioning
confidence: 99%
“…NaB is another boron derivative that is known to be an effective agent in obesity 10 , wound healing 11 , cryopreservation 12 and cancer 13 . NaB showed metabolic reprogramming related to SIRT3 activity in Hep3B cell lines 14 .…”
Section: Introductionmentioning
confidence: 98%